Julia Kristeva : psychoanalysis and modernity - Beardsworth, Sara (SUNY series in gender theory., 2004)
"This is the first systematic overview of Julia Kristeva's vision and work in relation to philosophical modernity. It provides a comprehensive and interdisciplinary analysis of her thought on psychoanalysis, art, ethics, politics, and feminism in the secular aftermath of religion. Sara Beardsworth shows that Kristeva's multiple perspectives explore the powers and limits of different discourses as responses to the historical failures of Western cultures, failures that are undergone and disclosed in psychoanalysis."--Jacket